Deep coverage whole genome sequences and plasma lipoprotein(a) in individuals of European and African ancestries - Seyedeh M. Zekavat (Nature Portfolio, 2018)
Circulating lipoprotein(a) is an important risk factor for cardiovascular disease and shows variability between different ethnic groups. Here, Zekavat et al. perform whole-genome sequencing in individuals of European and African ancestries and find ancestry-specific genetic determinants for lipoprotein(a) levels.